Prevalence and Demographic Risk Factors of Mycobacterium tuberculosis Infections in Captive Asian Elephants (Elephas maximus) Based on Serological Assays - Angkwanish, Taweepoke; Vernooij, Hans J. C. M.; Sirimalaisuwan, Anucha; Charernpan, Pattara; Nielen, Mirjam; Rutten, Victor P. M. G. (Frontiers in Veterinary Science, 2021)
To address putative TB statuses of elephants and to identify and quantify potential demographic risk factors for TB, three ELISAs specific for different mycobacterial antigens (ESAT6, CFP10, MPB83) and the TB Stat-Pak assay were used as surrogate serological markers for TB infection in elephants. In view of the low number of animals of which the infected status could be confirmed (4 out of 708) Latent Class Analyses of TB serology test outcomes was used to predict the putative TB status of each of 708 elephants as positive (17.3%), inconclusive (48.7%), or negative (34%) when assessed on a population basis. Correlation between test per-formance of the individual assays was high between the ELISAs, but low with that of the TB Stat-Pak assay. Risk factors, assessed based on cut off values for each of the ELISAs deter-mined by ROC analysis, included sex, BCS, age, working time, feed type, management system, camp size and region. Old age elephants were more likely to show a positive TB serology test outcome, than younger ones. Elephants working 7 hours per day and the ones in good condi-tion BCS (7-11) were less likely to be positive in TB serology testing. In addition, fewer ani-mals in the large camp size (31-50 elephants) were found to be positive in ELISA tests, com-pared to elephants in the other camp sizes. In this study, the North region had the lowest per-centages of elephants with positive TB test outcome, the West region and to a lesser extend the other regions showed clearly higher percentages of positive animals. Even though assays used in the present study have not been validated yet, results obtained showed promise as diagnostic or screening tests. For diagnostic purposed of animals suspected to be infected, the ELISA test can be used in parallel. For screening of complete camps for presence or absence of infection, a single ELISA test can be utilized.